Fish Seed Rearing to Improve Qualitative Production of Fish Farmers: A Review - Dr. Sharad Raosaheb Surnar (International Journal of Scientific Research in Science and Technology, 2026)
This review synthesizes current knowledge on fish seed rearing practices to enhance qualitative production in aquaculture systems. The global aquaculture production exceeding capture fisheries, the quality of fish seed has become a critical condition of fish farming success and profitabal. Present study examines nursery and rearing protocols, feeding strategies, water quality management and disease prevention. This study details the successful rearing and production of carp seed using a portable Fibre Reinforced Plastic (FRP) tank in the Jalkot region of Latur district, Maharashtra. Indian major carp spawn was utilized to sustain seed production. The experiment achieved a 90% survival rate within 20-30 days of cultivation. The FRP tank's high portability, simple installation, and low cost demonstrate its suitability for adoption by fish farmers in the Marathwada region, providing a viable and sustainable method for increase fish seed to support local aquaculture. The findings provide practical recommendations for fish farmers to optimize seed production, improve survival and growth rate and enhance overall productivity in aquaculture operations.
Keywords: Carp spawn; fry; survival; Growth & FRP tank